Participatory fisheries management for livelihood improvement of fishers in Phewa Lake, Pokhara, Nepal - Gurung, Tek B; Wagle, Suresh K; Bista, Jay D; Joshi, Purushottam L; Batajoo, Rabindra; Adhikari, Pushpa; Rai, Ash K (Himalayan Journal of Sciences, 2007)
This paper deals with the participatory fisheries management program, aimed at and successful in livelihood improvement of fisher community known as ‘Pode’ or ‘Jalari’ living near Phewa Lake, Pokhara, Nepal. The community, traditionally depending on fishing activities for their livelihood, led a nomadic life along the rivers and lakes, carrying cast nets to feed their families. In the early 1960s, when the fish catch declined due to over fishing, the Pode’s only source of livelihood was threatened. Meanwhile, the Fisheries Development Center, now Agriculture Research Station (Fisheries), was established in Pokhara in 1962 with the objective of assisting the poorest fishing communities through cage fish culture and open water fisheries. To begin with, each family was enabled to buy a single 50 m3 cage in order to start farming fish; the loans were underwritten by the local Agriculture Development Bank. The total fish production from Phewa Lake in 2001 was estimated at 98 mt (224 kgha-1: 52 mt from cage culture and 46 mt from open water recapture fisheries). The income from fish production is shared among local fisher families; it has brought substantial changes in the livelihood of the fisher community. A few years ago, it was difficult to find a literate member of the Pode community, but these days many children attend school and some even college. The community has realized the importance of lake resources and devised a code of conduct for sustainable fishery. The improvement on livelihood of fisher community is attributable to the combination of participatory fisheries management with their traditional skill on fish handling as well as their easy access. Apart from supporting in livelihood of poor communities, participatory fisheries management also contributes in maintaining ecological balance of aquatic ecosystems. Key words: ‘Pode’, sustainable fishery, Phewa, cage culture, livelihood Himalayan Journal of Sciences 3(5) 2005 p.47-52